Survival outcome and growth of children with langerhans cell histiocytosis: A 20 years experience from a single institution in Malaysia / Ooi Li Lyn - Ooi , Li Lyn (2017)
Langerhans cell histiocytosis (LCH) is a rare clonal proliferation of immunophenotypically and functionaUy immature LCH cells which lead to organ damage. The present study describes the data on LCH collected in a single institution in Malaysia over a 20-year period. Method: This is a retrospective study of patients with LCH being treated in paediatric oncology unit, UMMC. Beginning from lst January 1997 to 31st December 2015, all new patients with a confirmed diagno is with biopsy' which demostrate CDla antigenic determinants on the surface of lesional cells, or ells expressed S 100 were included. Patient characteristics, presenting clinical features, date of diagnosis, imaging finding, biopsy report, treatment received, outcome, final height when last seen and date of last seen were recorded in a standard data collection sheet. Results: We analyzed 53 patients who were diagnosed with LCH within the study period. Median age of diagnosis was 24 months (range 0 to 10 years old). Bone was the most frequently affected organ (70%) followed by liver (40%). 20 patients (38%) had single-system involvement (SS), 6 (11 %) with multisystem (MS) disease without risk organ involvement (MS-RO-), and 27 (51 %) multisystem disease with risk organ involvement (MS-RO+). The 5-year overall survival (OS) rates in the SS, MS-RO-, and MS-RO+ groups were 100%, 100%, and 51.8%, respectively (P<0.001). Subjects with MS-RO+ had poorer weight and height at baseline and follow-up than subjects with SS and MS-RO-. Mean height SDS and mean weight SDS were lower in subjects with concomitant DI than those without DI at baseline. Conclusion: Similar disease and patient characteristic were observed in our children with LCH compared to other centers. Patients in our center are significantly having poor growth which needs urgent attention. Although our results were inferior compared to the major trials, the overall outcome remain optimistic.